2010
DOI: 10.1007/s00134-010-2073-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term survival by treatment among patients hospitalized with acute heart failure: the global ALARM-HF registry using propensity scoring methods

Abstract: In terms of in-hospital survival, a vasodilator in combination with a diuretic fared better than treatment with only a diuretic. Catecholamine inotropes should be used cautiously as it has been seen that they actually increase the risk for in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
138
1
19

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(167 citation statements)
references
References 42 publications
9
138
1
19
Order By: Relevance
“…The results of this study alone, given the lack of a strong statistically significant result, and the poor methodological quality of the included studies, may not be sufficient to drive a change in clinical practice. It should be noted that the results of this study are in accord with large observational studies that have also suggested harm associated with use of dobutamine in patients with severe heart failure [47,48]. Taken together, this evidence should cause clinicians to reconsider their use of dobutamine in patients with heart failure, particularly those most at risk of the adverse effects, those with underlying ischaemic heart disease.…”
Section: Nrsupporting
confidence: 78%
“…The results of this study alone, given the lack of a strong statistically significant result, and the poor methodological quality of the included studies, may not be sufficient to drive a change in clinical practice. It should be noted that the results of this study are in accord with large observational studies that have also suggested harm associated with use of dobutamine in patients with severe heart failure [47,48]. Taken together, this evidence should cause clinicians to reconsider their use of dobutamine in patients with heart failure, particularly those most at risk of the adverse effects, those with underlying ischaemic heart disease.…”
Section: Nrsupporting
confidence: 78%
“…i obserwacji oDległej w okresie zwiększonego ryzyka Pacjenci przyjęci z AHF mogą zostać wypisani do domu [552]:…”
Section: Kryteria Wypisywania Ze Szpitalaunclassified
“…Observational data have demonstrated that titrated nitroprusside with conversion to combinational treatment with oral hydralazine and nitrates is feasible and potentially associated with better outcomes in advanced decompen- sated HF patients with low cardiac output who are normo-or hypertensive [50,51] . Afterload reduction in decompensated HF is further supported by a retrospective analysis of 4,953 patients, which used propensity-matching to demonstrate improved survival with vasodilator therapy versus increased mortality with inotrope therapy [52] . However, it is worth mentioning that the notion of increased mortality with inotropes mainly comes from data with β-agonists (i.e., dopamine and dobutamine) and phosphodiesterase-3 inhibitors (i.e., milrinone), with a potentially better safety profile of the calcium-sensitizer levosimendan, making the latter the preferred inotrope to use in decompensated HF patients with low cardiac output and arterial hypotension [48,49,53] .…”
Section: Increasing the Effective Circulatory Volumementioning
confidence: 99%